Effects of Neoadjuvant Chemotherapy and Radiotherapy on Flap Perfusion in a Novel Mouse Model Using Standard Clinical Assessment and Near-Infrared Fluorescence Angiography - Tushar Ramesh; Lindsay S Moore; Neel Patel; Kiranya Tipirneni; Jason M Warram; Jillian R Richter; Erika M Walsh; Geoffrey P Aaron; Anthony B Morlandt; Brian B Hughley; Eben L Rosenthal (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Purpose: Minimizing surgical morbidity after local flap reconstruction is important in the management of cutaneous defects. Controversy exists in current literature regarding the effects of radiation and chemotherapy on flap perfusion. Neoadjuvant treatments can damage the microvasculature of the surgical bed through fibrosis, endothelial cell damage, and reduced cell proliferation, which collectively increase the likelihood of postoperative flap failure. The aim of this study is to examine the effects of neoadjuvant radiation and chemotherapy on skin flap perfusion.  Methods: Animals were divided into three groups: control (no treatment, n=4), radiation group (36- Gy administered to dorsal skin, n=4), and chemotherapy group (2 mg/kg IP cisplatin, n=4). Treatments were performed 15 days prior to random-pattern dorsal flap surgery, with a flap length-to-width ratio of 4:1 (4x1cm2). Flap perfusion was assessed via laser-assisted (Luna, Novadaq) indocyanine green dye angiography and standard clinical assessment.  Results: Fluorescence imaging was used to quantify flap perfusion as a fraction of healthy skin perfusion. Chemotherapy group flaps had poorer distal end perfusion than radiation or control group flaps (56% vs. 69% and 71%, respectively) on post-operative day (POD) 1. Clinical assessment of flap perfusion by experienced surgeons on POD2 found chemotherapy group fl aps to be least viable. By POD5, 100% of chemotherapy group flaps had experienced complete flap loss as measured by clinical evaluation and perfusion imaging.  Conclusion: Flaps receiving neoadjuvant chemotherapy performed worse than those receiving local radiotherapy or no treatment. We demonstrate the detrimental effect of neoadjuvant chemotherapy on fl ap viability in this pre clinical murine model.